Radiation therapy for prostate cancer: What's the best in 2021. Issue 1 (February 2022) - Cellini, Francesco; Tagliaferri, Luca; Frascino, Vincenzo; Alitto, Anna Rita; Fionda, Bruno; Boldrini, Luca; Romano, Angela; Casà, Calogero; Catucci, Francesco; Mattiucci, Gian Carlo; Valentini, Vincenzo
Radiotherapy is highly involved in the management of prostate cancer. Its features and potential applications experienced a radical evolution over last decades, as they are associated to the continuous evolution of available technology and current oncological innovations. Some application of radiotherapy like brachytherapy have been recently enriched by innovative features and multidisciplinary dedications. In this report we aim to put some questions regarding the following issues regarding multiple aspects of modern application of radiation oncology: the current application of radiation oncology; the modern role of stereotactic body radiotherapy (SBRT) for both the management of primary lesions and for lymph-nodal recurrence; the management of the oligometastatic presentations; the role of brachytherapy; the aid played by the application of the organ at risk spacer (spacer OAR), fiducial markers, electromagnetic tracking systems and on-line Magnetic Resonance guided radiotherapy (MRgRT), and the role of the new opportunity represented by radiomic analysis.